1984
DOI: 10.1007/bf01963584
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte membrane lipid peroxidation in iron deficiency anemia

Abstract: Erythrocytes from normal subjects and from cases of iron deficiency anemia were exposed to hydrogen peroxide and the extent of membrane lipid peroxidation studied. Significantly less peroxidation was observed in intact anemic erythrocytes compared to normal. However, when isolated membrane lipids were subjected to peroxidation, there was no significant difference between the two groups. It is unlikely that lipid peroxidation per se plays a major role in the reported decrease in red cell life-span in iron defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…They suggested that increased antioxidant capacity was a compensatory factor for increased oxidant stress (16,18). In this study, total antioxidant capacity in patients with IDA was lower than controls.…”
Section: Discussionmentioning
confidence: 90%
“…They suggested that increased antioxidant capacity was a compensatory factor for increased oxidant stress (16,18). In this study, total antioxidant capacity in patients with IDA was lower than controls.…”
Section: Discussionmentioning
confidence: 90%
“…The majority of studies on oxidative stress in IDA are based on lipid peroxidation measurements, and their results are contradictory. It has been determined that red blood cell susceptibility to in vitro oxidation is increased in IDA patients [4,32]; however, some authors have suggested that there is no evidence of increased susceptibility of red blood cells to lipid peroxidation [1,23]. Biomolecular targets of free radicals extend beyond lipids, and DNA oxidation may have more severe consequences.…”
Section: Discussionmentioning
confidence: 96%
“…Although conflicting results have been reported [8,10], it is generally accepted that oxidative stress is increased through increase in oxidant levels and/or decrease in antioxidant enzyme capacities in IDA. Generally, decreased GSH-Px activity along with normal or increased SOD and CAT activity are the main findings in IDA [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidant levels and antioxidant enzyme activities such as SOD, GSH-Px and CAT have been evaluated in several studies [8][9][10][11][12][13][14]. Although conflicting results have been reported [8,10], it is generally accepted that oxidative stress is increased through increase in oxidant levels and/or decrease in antioxidant enzyme capacities in IDA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation